Delayed Interferon Type 1-Induced Antiviral State Is a Potential Factor for Hemorrhagic Fever With Renal Syndrome Severity. (21st December 2017) - Resman Rus, Katarina; Korva, Miša; Bogovič, Petra; Pal, Emil; Strle, Franc; Avšič-Županc, Tatjana
Abstract : Puumala, but not Dobrava, virus activated IFN type 1-induced antiviral state and IFNβ, STAT-1, and MxA were upregulated in stimulated peripheral blood mononuclear cells. Delayed IFN type 1-induced antiviral state could contribute to hemorrhagic fever with renal syndrome severity. Abstract: Hantaviruses cause hemorrhagic fever with renal syndrome (HFRS) in Europe and Asia. Interferon (IFN) responses play an important role in HFRS pathogenesis and early IFN-β response is delayed by pathogenic hantaviruses. The severity of HFRS caused by Dobrava virus (DOBV) and Puumala virus (PUUV) varies. Our aim was to determine whether differences in early activation of IFN type 1-induced antiviral state influence HFRS severity. Peripheral blood mononuclear cells (PBMCs) from healthy donors and HFRS patients were stimulated with DOBV or PUUV and expression of selected genes was measured. PUUV, but not DOBV, activated IFN type 1-induced antiviral state in stimulated PBMCs, and IFNβ, STAT-1, and MxA were highly upregulated. Upregulation of MxA was earlier in acute-phase PBMCs and higher in convalescent-phase PBMCs from patients with mild compared with severe PUUV infection. Our study showed that delayed IFN type 1-induced antiviral state could contribute to HFRS severity, particularly in PUUV infection.